THE INFLUENCE OF RETAIL SERVICE QUALITY ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE IN ALFAMIDI MEDAN CITY - Finella Gilda Novia Sembiring; Iskandarini; Sugih Arto Pujangkoro (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Research purposesTo analyze whether retail service quality, retail service quality influences customer satisfaction and customer loyalty at Alfamidi in the city of Medan.The type of research that the author uses in the research is quantitative research. This research was conducted at Alfamidi in the city of Medan, starting from June to August 2023. The population in this research were customers shopping at Alfamidi in the city of Medan in the surrounding Medan Amplas area, namely Alfamidi SM Raja 3, Alfamidi Selambo, Alfamidi Amplas, and Alfamadi Super SM Raja who used Alfamidi member cards amounted to 1,970 customers for a month, which became the research population. The sampling carried out in this research used purposive sampling. So the resulting sample is 220 samples. With the results of Retail Service Quality, it has a positive and significant effect on Customer Satisfaction at Alfamidi, Medan City. Retail Service Quality has a positive and significant effect on Customer Loyalty at Alfamidi, Medan City. Customer Satisfaction has a positive and significant effect on Customer Loyalty at Alfamidi, Medan City. Customer Satisfaction mediates the influence of Retail Service Quality on Customer Loyalty in Alfamidi, Medan City.